2019
DOI: 10.3390/ijms20215375
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Research on Diabetes by Human Nutriomics

Abstract: The incidence and prevalence of diabetes mellitus (DM) have increased rapidly worldwide over the last two decades. Because the pathogenic factors of DM are heterogeneous, determining clinically effective treatments for DM patients is difficult. Applying various nutrient analyses has yielded new insight and potential treatments for DM patients. In this review, we summarized the omics analysis methods, including nutrigenomics, nutritional-metabolomics, and foodomics. The list of the new targets of SNPs, genes, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…With the increasingly popularization of the concept of precision medicine, the accurate prediction of patients' prognosis is becoming much more critical [13,14]. Many previous studies have shown the accurate predictive ability of nomograms for predicting overall survival in patients with low-grade endometrial stromal sarcoma [10], adrenocortical carcinoma [15], hepatoblastoma [16], and many other system cancers.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasingly popularization of the concept of precision medicine, the accurate prediction of patients' prognosis is becoming much more critical [13,14]. Many previous studies have shown the accurate predictive ability of nomograms for predicting overall survival in patients with low-grade endometrial stromal sarcoma [10], adrenocortical carcinoma [15], hepatoblastoma [16], and many other system cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the complexity of the human body and its interplay with food, it is conceivable that holistic molecular analyses of food–body interactions (i.e., nutri-omics) are essential to understanding the effects of nutrients [ 143 ]. Several studies have pointed to diet–gene interactions affecting glucose metabolism and being linked to diabetes (reviewed in [ 144 ]). Studying dietary interventions and personalized nutrition could reveal certain diet types, which could help prevent adverse fetal outcomes caused by maternal diabetes.…”
Section: Microbiomics and Nutriomics Studies Addressing Gdm Effects On Offspringmentioning
confidence: 99%
“…Using "omics" technologies, several molecular events, i.e., pathways activation, epigenome stability, and protein expression, caused by nutrients intake have been identified. Now, the innovative goal of nutrition research is focused on identifying the relationship between food constituents and molecular targets [29,30]. This new approach of nutritional intervention, based on the molecular action of food and not only on nutritional value of food, represents the crucial therapeutic strategy in the T2DM and CVD.…”
Section: New Dietary Interventions In T2dm/cvd Managementmentioning
confidence: 99%
“…For T2DM patients, reduced daily calorie intake is the gold standard of dietary therapeutic interventions [31]. Studies performed using different animal models and human clinical trials have demonstrated that caloric restriction (CR), a nutritional approach based on caloric intake decrease (between 20 and 40%) without modifying the balance of micro/macronutrients, ameliorates cardiometabolic conditions and extends lifespan [30,31].…”
Section: From Caloric Restriction To Caloric Restriction Mimeticsmentioning
confidence: 99%